Chitosan–polydopamine hydrogel complex: a novel green adhesion agent for reversibly bonding thermoplastic microdevice and its application for cell-friendly microfluidic 3D cell culture. Issue 19 (1st September 2020) - Trinh, Kieu The Loan; Le, Nguyen Xuan Thanh; Lee, Nae Yoon
Abstract : A chitosan–polydopamine hydrogel complex was introduced as an UV-assisted biocompatible adhesion agent for fabricating a PMMA microdevice employed in spheroid formation. Abstract : Owing to biocompatible characteristics and supporting cell growth capability, hydrogels have been widely used for scaffold fabrication and surface coating for cell culture. To employ the advantages of hydrogels, in the present study, we introduce a biocompatible chitosan (CS)–polydopamine (pDA) hydrogel complex as a green adhesion agent for the reversible bonding of thermoplastics assisted by UV irradiation. Poly(methyl methacrylate) (PMMA) substrates were bonded due to the covalent bond network formed between the amine groups of either CS or pDA in the hydrogel complex and the aldehyde groups of the oxidized PMMA surface via the Schiff-base reaction during the UV irradiation. Furthermore, the introduced method allowed for reversible bonding, which is highly appropriate for the fabrication of microdevices for cell-related applications. Surface characterizations such as water contact angle measurement, scanning electron microscopy analysis (SEM), atomic force microscopy analysis (AFM), and Fourier-transform infrared microscopy analysis (FTIR) were performed to confirm the successful coating of the hydrogel complex on the PMMA surface. Moreover, the bonding between two PMMAs or PMMA with other thermoplastics was successfully investigated with high bond strengths ranging from 0.4 to 0.7 MPa. The potential for reversible bonding of this method was verified by repeating the bonding/debonding cycle of the bonded PMMAs for three times, which maintained the bond strength at approximately 0.5 MPa. The compatibility of the bonding method in biological applications was examined by culturing mesenchymal stem cells (MSCs) inside a microchannel where multiple uniform-sized MSC spheroids were successfully formed. Then, spheroids were harvested for off-chip experiments enabled by the reversibility of the introduced bonding strategy. The bonding strategy employing a green hydrogel complex as a cell-friendly and eco-friendly adhesion agent could have a high impact on the fabrication of microdevices suitable for advanced organ-on-a-chip studies.